European merger control policy : private interests, policy communities and entrepreneurship - Shea, Eric J. (Trinity College (Dublin, Ireland). Department of Political Science, 2005)
The intent of this thesis was to reconcile the divergent strands in the existing literature on European competition and merger policy by providing a systematic analysis of the development and implementation of the European Merger Control Regulation (MCR). The analysis was not confined only to the policy-making process but also examined how policy goals were put into practice. By examining various case studies and trends within the policy area, policy goals were compared with policy output. Consequently, a unique aspect of this study is that it strikes a balance between the political, economic, and legal dimensions of European merger policy.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin